The social theories of practice underpinning the strategy-as-practice - Nicolini, Davide (Henry Stewart Talks, 2012)
Practice, Practice theory, Giddens, Bourdieu, Ethnomethodology, Schatzki, Practice-based studies, Strategy-as-Practice, Practice-history, Activity, Theory -Zooming-in, Zooming-out